Transforming the legal education in the era of IR 4.0 - Amirnuddin, Puteri Sofia; Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali (2019)
The recent technological advances trigger the emergence of the Industry Revolution 4.0 (IR 4.0) which is very dynamic and progressive to the extent most of the major industries in the world have no option left but to transform the industry accordingly in order to adapt to the changes in the IR 4.0 era. Hence, this paper aims at exploring how the legal education offered at higher learning institutes can be transformed to be in line with the IR 4.0 in an efficient manner by maintain the quality. Tertiary education system should catch up with this progress to ensure that modern legal education would be fully modified and concurrent with it. So far, there is a significant delay in transforming legal educational services offered at universities, colleges and other higher learning institutes with regard to fields of study, subjects offered, teaching methods; assessment methods, among others. Despite the fact that it is complex, for the time being, to transform the legal education to be in line with the IR 4.0, it will benefit the society unprecedentedly for long run as it is the “game changer” of this era.